(untitled) (Research, Society and Development, 2021)
The objective of the article is to present the Brazilian government’s indexes of ideological orientation to face the COVID-19 pandemic, obtained as a result of the development of research by the Laboratory of Fundamental Psychopathology in Studies of Subjectivity and Humanitarian Emergency. In it, the term psychosocial and clinical history of humanitarian emergencies was created to designate the systematized record of research, information, government actions, case studies, testimonies, which make it possible to trace a story about the impact of the context of humanitarian emergencies - and, more specifically, COVID-19 – in the mental health of populations. The data obtained from the systematization were privileged: 1. Theoretical references of Sigmund Freud’s thought on the impact of the humanitarian emergency of World War I on subjective functioning; 2. Information and actions of countries and the Brazilian government in relation to the COVID-19 pandemic, based on the search for national and international scientific articles, official documents from FIOCRUZ, WHO, UN, IHR and public statements by federal authorities in newspapers , social networks and video platforms. Data were collected between February 27, 2020 and May 27, 2021, based on the following descriptors: COVID-19; Humanitarian Emergency; Health and health safety policies; Mental health; Subjectivity; Humanitarian Emergency; Health and health safety policies; Mental health; Subjectivity. The results obtained were organized into four axes: the eruption of COVID-19; the denomination of humanitarian emergency and the impact of COVID-19 on mental health; the financial contribution to science, technology and innovation regarding COVID-19; Science and public health and health security policies. They indicate the high ideological orientation, interfering in the formulation of public health policies to fight the pandemic. The results consisted in the formulation of ten indexes of ideological orientation of the Brazilian government to face the pandemic. They indicate a high ideological orientation, directly interfering in the formulation of public health and health security policies for their prevention and combat.